Huaraz city urban growth modeling through logistic regression - Villanueva Ramírez, Ricardo Ray (2021)
In 1941, Huaraz city was affected by a flood from Palcacocha glacier lagoon, thenceforth the city grew significantly occupying areas exposed to floods. For future risks analysis, city growth prospective evaluation is necessary, being logistic regression a widely used technique. Using geomatic tools, aerial and satellite photographs from 1948, 1962, 1977, 2011 and 2018 were visually and geometrically corrected taking cadastral map 1:10,000 as base cartography. With complementary field work polygons of urban/populated areas were obtained within a 25 km² analysis zone, with which the historical spatial trend and growth characteristics were analyzed in relation to variables such slope, altitude, distance from city middle center, direction growth and point density; which were used as independent variables in the regression logistic model being the dependent the 2018 urban/populated coverage. Between 1948 and 2018 Huaraz grew 598% in South-North direction with bias towards East. Excluding 2018 urban/populated area, 21% of the analysis zone has probabilities of housing new urban/populated areas greater than 0.2, prevailing 0.2 to 0.4 probabilities with 11%.